ChatGPT in university education: An integrated perspective for personal well-being - Danna, Edvige (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
The role of digital technologies in education is becoming increasingly important for both teaching and learning, affecting attention spans. This research examines university students’ views on using artificial intelligence in education, highlighting its positive aspects and the teacher’s guiding role to promote cognitive and social well-being.